2013
DOI: 10.1021/bi401344f
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem I Reduction in Diatoms: As Complex as the Green Lineage Systems but Less Efficient

Abstract: Diatoms occupy a key branch in the evolutionary tree of oxygen-evolving photosynthetic organisms. Here, the electron transfer reaction mechanism from cytochrome c 6 to photosystem I from the diatom Phaeodactylum tricornutum has been analyzed by laser-flash absorption spectroscopy. Kinetic traces of photosystem I reduction fit to biphasic curves, the analysis of the observed rate constants indicating that electron transfer occurs in a cytochrome c 6 /photosystem I transient complex, which undergoes a reorganiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(52 citation statements)
references
References 59 publications
9
42
1
Order By: Relevance
“…Recently, the ET reaction mechanism from Cyt to PSI from the diatom Phaeodactylum tricornutum has been first analyzed by laser-flash absorption spectroscopy [17], indicating that ET occurs within a Cyt/PSI transient complex that undergoes a reorganization process from the initial encounter complex to the optimized final configuration, as already described in "green" PSI systems. However, the results also demonstrated that the "red" Phaeodactylum system possesses a lower efficiency than "green" systems, both in the formation of the properly arranged [Cyt-PSI] complex and in the electron transfer itself [17]. In addition, the relatively weak electrostatically attractive nature of the Cyt/PSI interaction seems to represent a compromise between the efficiency in the ET process and the need for a fast exchange of the protein donor [17].…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Recently, the ET reaction mechanism from Cyt to PSI from the diatom Phaeodactylum tricornutum has been first analyzed by laser-flash absorption spectroscopy [17], indicating that ET occurs within a Cyt/PSI transient complex that undergoes a reorganization process from the initial encounter complex to the optimized final configuration, as already described in "green" PSI systems. However, the results also demonstrated that the "red" Phaeodactylum system possesses a lower efficiency than "green" systems, both in the formation of the properly arranged [Cyt-PSI] complex and in the electron transfer itself [17]. In addition, the relatively weak electrostatically attractive nature of the Cyt/PSI interaction seems to represent a compromise between the efficiency in the ET process and the need for a fast exchange of the protein donor [17].…”
Section: Introductionmentioning
confidence: 86%
“…However, the results also demonstrated that the "red" Phaeodactylum system possesses a lower efficiency than "green" systems, both in the formation of the properly arranged [Cyt-PSI] complex and in the electron transfer itself [17]. In addition, the relatively weak electrostatically attractive nature of the Cyt/PSI interaction seems to represent a compromise between the efficiency in the ET process and the need for a fast exchange of the protein donor [17].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations